The critical roles of errors and individual differences in bilingual translation. Issue 4 (August 2019) - TOKOWICZ, NATASHA
Abstract : Multilink moves the field a step forward in being able to make clear predictions about how a bilingual's languages interact in a variety of tasks. It addresses some shortcomings of the BIA (Dijkstra, van Heuven & Grainger, 1998 ) and BIA+ (Dijkstra & van Heuven, 2002 ) models, which did not explain performance from bilinguals of varied proficiency levels or on translation tasks. However, there are still gains that can be made – Dijkstra, Wahl, Buytenhuijs, van Halem, Al-jibouri, de Korte, and Rekké (2018 ) themselves point out that there are additional ways in which they plan to expand the model.